Building Trust with Agricultural and Rural Decision-Makers through Engaged Climate Educational Models in the Rural U.S. Central Great Plains - Champion, Benjamin L.; Devlin, Daniel L.; Rice, Charles W.; Harrington, John A., Jr.; Kahl, Daniel W.; Spears, Jacqueline D.; Steffensmeier, Timothy R.; Washburn, Shannon G.; Bruning, Roger; Pytlik Zillig, Lisa; Abdel-Monem, Tarik L.; Hu, Qi; et al. (Kansas State University, 2012)
Potential climate change impacts on Central Great Plains (CGP) agricultural production are profound and highly likely to affect both national and global food supplies and related social and economic systems. Predicted climate changes include increasing temperatures with more variability including, greater precipitation events, longer and more frequent heat waves. These changes will impact agricultural production, water supply, and human health. Three annual crops, corn, sorghum, and wheat, which collectively account for 81 million hectares of agricultural land in the U.S., are concentrated in the Midwest and Central Great Plains. These crops are the mainstay for U.S. agriculture and account for $30.1 billion of agricultural production annually. The CGP also has been identified as one of the few regions around the globe that has a high degree of coupling of climate to soil moisture conditions, suggesting that any changes in precipitation will amplify climate feedbacks. This increases the level of uncertainty regarding the effects of climate change on production agriculture. Despite the fact that both Nebraska and Kansas are heavily dependent upon agriculture for their economic well-being, rural citizens’ responses to climate change remain mixed. Regional research has found that most rural Nebraskans felt at least fairly well informed about climate change (71%), believed climate change was happening (58%), and were concerned or very concerned about climate change impacting the U.S. (60%), but other research indicates that sizable numbers of producers say that weather and climate forecasts do not influence their agricultural decisions (e.g., ranging from 9% to 42% depending on the specific forecast product and agricultural decision). Focus groups from our Phase I partnership conducted with three sets of stakeholders (agricultural producers, rural community members, and agriculture/science educators representing future agricultural producers/rural community members) suggest these stakeholder group members were eager to learn more about climate and how it might change, but that their purposes, goals and attitudes toward the information vary widely. Different stakeholder groups want access to different types of information as well as how to use that information for different purposes. Moreover, they want increased access to data such that it allows them to decide for themselves how the data could be useful to them. Despite these differences, all the focus group stakeholders desire information that they can trust, is frequently and quickly updated, and easy to access. Most of all, they want locally relevant information. Conclusions from Phase I emphasize locally relevant, inquiry-based approaches with multiple points of access to the development and delivery of educational programs on climate change. We have developed a larger research and implementation framework outlining these multiple points of entry for different stakeholder audiences and a plan for programming across the three stakeholder groups based on this framework. Information about project personnel, partners, and other project information can be found at the project website: www.ksu.edu/cgp-ccep
Keywords: Climate change; Focus groups; Stakeholders; Education programs; Production agriculture